Prevalence of renal failure patients with three-weekly standardized dialysis session at university teaching hospital of Butare - Ndayisenga, Leonard; Nsanzabera, Charles; Hitimana, Eugene (International Journal Of Community Medicine And Public Health, 2020)
Background: Dialysis is a treatment of choice to alleviate severe complications of end-stage renal disease. Renal failure is the most prevalent worldwide among diabetic, hypertensive, and where infective diseases are frequent. The study aimed to assess the prevalence of patients having three standard dialysis sessions weekly at University Teaching hospital of Butare dialysis centre from June 2013 to June 2014. Methods: A descriptive cross-sectional study used routine hospital data from university teaching hospital of Butare dialysis unit and its size were 110 patients who fulfilled the study inclusion criteria. Secondary data were collected using a checklist with different variables like age, sex, profession, health insurances, acute renal failure, chronic renal failure, diabetes mellitus, hypertension, glomerular disease sepsis, severe dehydration, frequency of dialysis per week and outcomes like renal recovery, death, stopping treatment and being referred. Data were analysed using SPSS software. Results: The findings showed that 40.9% of patients received three or above dialysis sessions per week and 59.1% of patients received less than three sessions per week. Conclusions: The study concluded on inadequacy dialysis treatment and recommended further studies to explore more about this inadequacy.